0024 Innovative approaches for developing collaborative research projects on suicide prevention: the icrc-s research training institute and community of practice. (26th April 2015) - Allison, Jennifer; Rodgers, Cynthia; Hunt, Rebekah
Abstract : Statement of purpose: The Injury Control Research Centre for Suicide Prevention (ICRC-S), a project of the University of Rochester Medical Centre and the Education Development Centre, seeks to create dialogue and collaboration among injury prevention professionals and researchers in order to generate new research projects that will advance knowledge about the public health approach to suicide prevention. Methods/Approach: This presentation will describe three approaches that the ICRC-S has implemented to support the development and implementation of collaborative research projects: (1) a five-day Research Training Institute (RTI), (2) a virtual Community of Practice (CoP) for peer learning and networking through interactive webinars, and (3) a mentoring process in which research teams comprised of both practitioners and researchers participate in bi-monthly conversations with ICRC-S faculty. The presentation will provide an in-depth description of each approach, examples of its impact, and an explanation of the challenges encountered and how those challenges have been addressed. Results: The three approaches described above have resulted in the development of nine new research projects in nine different states. State health department injury/suicide prevention directors or their staff have been involved in these efforts from the inception. Information about these research projects will be shared during the presentation. Conclusions: The approaches described in this presentation provide injury prevention professionals and researchers with a shared body of knowledge and skills in suicidology, public health and prevention, and relevant research methodologies. Significance and contribution to the field: The Research Training Institute, Community of Practice, and mentorships have created collaborative links between the injury prevention and suicide research communities so that the perspectives, knowledge, and skills of each inform the work of the other, and they support the development of new research projects that will advance suicide prevention.